Activation of heterotrimeric G proteins by a high energy phosphate transfer via nucleoside diphosphate kinase (NDPK) B and Gβ subunits: specific activation of Gsα by an NDPK B·Gβγ complex in H10 cells - Hippe, Hans-Jörg; Lutz, Susanne; Cuello, Friederike; Knorr, Katrin; Vogt, Achim; Jakobs, Karl-Heinz; Wieland, Thomas; Niroomand, Feraydoon (The journal of biological chemistry, 2003)
Formation of GTP by nucleoside diphosphate kinase (NDPK) can contribute to G protein activation in vitro. To study the effect of NDPK on G protein activity in living cells, the NDPK isoforms A and B were stably expressed in H10 cells, a cell line derived from neonatal rat cardiomyocytes. Overexpression of either NDPK isoform had no effect on cellular GTP and ATP levels, basal cAMP levels, basal adenylyl cyclase activity, and the expression of G(s)alpha and G(i)alpha proteins. However, co-expression of G(s)alpha led to an increase in cAMP synthesis that was largely enhanced by the expression of NDPK B, but not NDPK A, and that was confirmed by direct measurement of adenylyl cyclase activity. Cells expressing an inactive NDPK B mutant (H118N) exhibited a decreased cAMP formation in response to G(s)alpha. Co-immunoprecipitation studies demonstrated a complex formation of the NDPK with Gbetagamma dimers. The overexpression of NDPK B, but not its inactive mutant or NDPK A, increased the phosphorylation of Gbeta subunits. In summary, our data demonstrate a specific NDPK B-mediated activation of a G protein in intact cells, which is apparently caused by formation of NDPK B.Gbetagamma complexes and which appears to contribute to the receptor-independent activation of heterotrimeric G proteins.